2010
DOI: 10.1590/s1519-69842010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Priority targets for environmental research in the Sinos River basin

Abstract: The Sinos River Basin is often mentioned as a highly degraded watershed. A series of impacts on water quality, soil and air has been reported in this environment on a recurring basis over the years. This situation of environmental degradation has its origins in a process of huge economic development uncoupled from environmental conservation concerns. The intense consequent urbanization observed for the municipalities within the watershed was not preceded by urban planning proper zoning. The time has arrived fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Spilki and Tundisi (2010) have reported that the Sinos River Basin is highly degraded due to a series of recurring impacts on water, soil and air quality over the years. This current situation of environmental degradation is the consequence of a process of huge economic development, arising from the footwear/leather sector and from intense urbanisation that took place with no concern for environmental conservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spilki and Tundisi (2010) have reported that the Sinos River Basin is highly degraded due to a series of recurring impacts on water, soil and air quality over the years. This current situation of environmental degradation is the consequence of a process of huge economic development, arising from the footwear/leather sector and from intense urbanisation that took place with no concern for environmental conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the creation of applicable measures of environmental recovery and conservation that might mitigate the impacts over the basin, one priority goal suggested in order to monitor the quality of the basin is to perform research on the toxic and genotoxic effects of pollutants on plants and animals (Spilki and Tundisi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Sinos River Basin (SRB) is often the subject of reports in the mass media and in scientific researches (Spilki and Tundisi, 2010;Blume et al, 2010;Costa and Schulz, 2010) because of environmental degradation scenarios in which it is inserted, mostly related to the low levels of water quality (Blume et al, 2010), mainly in the lower section of the basin, where the Schmidt Stream is found. This situation is alarming, since the Sinos River is the main source of public water supply in the region.…”
Section: Introductionmentioning
confidence: 99%
“…According to Spilki and Tundisi (2010), the Sinos River basin is frequently reffered to as largely degraded; a series of impacts on the quality of the water, soil and air have been reported for this area over the last years. In the present study, this community was characterized by monitoring water macroinvertebrates, and it theoretically reflects the environmental conditions.…”
Section: Locaismentioning
confidence: 99%